The study of co-relation of pap smear with colposcopy and histopathology in sexually active woman with unhealthy cervix - Dhama, Vandana; Minz, Tulika; Chaudhary, Rachna; Singh, Shakun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Unhealthy cervix is a group of cervical lesions, mostly chronic. Cervical cancer is the second most frequent cancer worldwide in women after breast carcinoma cervical cancer is a preventable and curable malignancy if identified and managed early. Primary objective was to study pap smear, colposcopy and histopathology in unhealthy cervix in sexually active woman with secondary objective to screen woman who have abnormal unhealthy, foul smelling cervical discharge. Methods: The present study was conducted in the department of obstetrics and gynecology L.L.R.M. medical College and associated SVBP hospital, Meerut from June 2019 to May 2020 with sample size of 70. Participant who fit the inclusion criteria were included in the study after taking a written and informed consent. The colposcopy finding was correlated with histopath findings of cervical biopsy that was undertaken. Results: Co relation of pap smear with colposcopy had sensitivity of 78% and specificity of 92% with positive predictive value of 52%and negative predictive value of 97%, p value less than 0.0001. The pattern of distribution of histopathological assessment with respect to the pap smear findings was significant statistically (p<0.0001). The proportion of patients with NILM on pap smear was significantly higher in the VILI negative category compared to the VILI Positive category (94.12% vs 77.78%, p=0.0525). In the present study, prevalence of CIN of any grade was detected in 8 (11.4%) cases. With CIN 1 in 5 (7.14%) and CIN2 in 2 (2.86%) and CIN3 in 1 (1.43%) case were seen. Conclusions: Several screening modalities are available of which pap smear is most widely used. colposcopy has been proven very useful to identify and guide the biopsy of dysplastic lesion.